Evaluation of the coverage and benefit incidences of food fortification in Mozambique. Executive summary - International Policy Centre for Inclusive Growth (IPC-IG) (International Policy Centre for Inclusive Growth (IPC-IG), 2019)
The main objective of this study is to evaluate the coverage of the National Food Fortification Programme (NFFP) in Mozambique regarding iron-fortified wheat and maize flours and vitamin A-fortified sugar and vegetable oil, as well as the benefit reach across population groups. A population-based cross-sectional household survey and laboratory tests to determine nutrient intake in food samples collected at households are the main source for the analysis.
Keywords: 330; Evaluation; Coverage; Benefit; Incidences; Food; Fortification; Mozambique